Clinical influence of preoperative factor XIII activity in patients undergoing pancreatoduodenectomy. Issue 11 (November 2017) - Watanabe, Nobuyuki; Yokoyama, Yukihiro; Ebata, Tomoki; Sugawara, Gen; Igami, Tsuyoshi; Mizuno, Takashi; Yamaguchi, Junpei; Nagino, Masato
Abstract: Background: The influence of decreased factor XIII (FXIII) activity on perioperative bleeding has been reported in some surgical procedures. The purposes of this study were to investigate the perioperative dynamics of FXIII in patients undergoing pancreatoduodenectomy and to clarify the effects of low preoperative FXIII activity on intraoperative bleeding and postoperative complications. Methods: Total of 43 patients who underwent a pancreatoduodenectomy were enrolled. The perioperative FXIII activities were measured, and their associations with intraoperative bleeding and postoperative outcomes were analyzed. Results: Fifteen patients (35%) had low FXIII activities (<70%, lower than the institutional normal range). The patients with preoperative FXIII activities <70% experienced significantly greater blood loss (median, 1309 mL) during surgery compared to those with FXIII levels of ≥70% (median, 710 mL) (p = 0.001). The postoperative morbidity rates, including pancreatic fistula, were comparable between the patients with FXIII activities <70% and those with FXIII activities ≥70%. The FXIII levels substantially decreased on postoperative day 1 and remained at low levels until postoperative day 7. Conclusion: Unexpectedly high proportions of patients undergoing pancreatoduodenectomy had low preoperative FXIII activities. Preoperative FXIII deficiency may increase intraoperative bleeding but had no influence on the postoperative outcomes.